ASB1 differential methylation in ischaemic cardiomyopathy: relationship with left ventricular performance in end‐stage heart failure patients - Ortega, Ana (ESC Heart Fail, 2018)
AIMS: Ischaemic cardiomyopathy (ICM) leads to impaired contraction and ventricular dysfunction, causing high rates of morbidity and mortality. Epigenomics allows the identification of epigenetic signatures in human diseases. We analyse the differential epigenetic patterns of the ASB gene family in ICM patients and relate these alterations to their haemodynamic and functional status. METHODS AND RESULTS: Epigenomic analysis was carried out using 16 left ventricular (LV) tissue samples, eight from ICM patients undergoing heart transplantation and eight from control (CNT) subjects without cardiac disease. We increased the sample size up to 13 ICM and 10 CNT for RNA sequencing and to 14 ICM for pyrosequencing analyses. We found a hypermethylated profile (cg11189868) in the ASB1 gene that showed a differential methylation of 0.26Δβ (P = 0.016). This result was validated by a pyrosequencing technique (0.23Δβ, P = 0.048). Notably, the methylation pattern was strongly related to LV ejection fraction (r = −0.849, P = 0.008), stroke volume (r = −0.929, P = 0.001), and end‐systolic and diastolic LV diameters (r = −0.743, P = 0.035 for both). ASB1 showed a down‐regulation in messenger RNA levels (−1.2‐fold, P = 0.039). CONCLUSIONS: Our findings link a specific ASB1 methylation pattern to LV structure and performance in end‐stage ICM, opening new therapeutic opportunities and providing new insights regarding which is the functionally relevant genome in the ischaemic failing myocardium.